Amustaline (S‐303) treatment inactivates high levels of Chikungunya virus in red‐blood‐cell components. Issue 3 (4th January 2018) - Aubry, M.; Laughhunn, A.; Santa Maria, F.; Lanteri, M. C.; Stassinopoulos, A.; Musso, D.
Abstract : Background and objectives: Chikungunya virus (CHIKV) infections have been reported in all continents, and the potential risk for CHIKV transfusion‐transmitted infections (TTIs) was demonstrated by the detection of CHIKV RNA‐positive donations in several countries. TTIs can be reduced by pathogen inactivation (PI) of blood products. In this study, we evaluated the efficacy of amustaline and glutathione (S‐303/GSH) to inactivate CHIKV in red‐blood‐cell concentrates (RBCs). Material and Methods: Red‐blood‐cells were spiked with high level of CHIKV. Infectious titres and RNA loads were measured before and after PI treatment. Residual CHIKV infectivity was also assessed after five successive cell culture passages. Results: The mean CHIKV titres in RBCs before inactivation was 5·81 ± 0·18 log10 50% tissue culture infectious dose (TCID50 )/mL, and the mean viral RNA load was 10·49 ± 0·15 log10 genome equivalent (GEq)/mL. No CHIKV TCID was detected after S‐303 treatment nor was replicative CHIKV particles and viral RNA present after five cell culture passages of samples obtained immediately after S‐303 treatment. Conclusion: Chikungunya virus was previously shown to be inactivated by the PI technology using amotosalen and ultraviolet A light for the treatment of plasma and platelets. This new study demonstrates that S‐303/GSH can inactivate high titres of CHIKV in RBCs.